2021
DOI: 10.18502/ijhoscr.v15i1.5247
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Iron Chelation Therapy and Its Determinants

Abstract: Background: Thalassemia is a chronic disease requiring lifelong treatment. The adherence to regular iron chelation therapy is important to ensure complication-free survival and good quality of life. The study aim to assess the adherence to iron chelation therapy (ICT) in patients with transfusion-dependent thalassemia (TDT), evaluate various causes of non-adherence and study the impact of non-adherence on the prevalence of complications secondary to iron overload. Materials and Methods: Patients with TDT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 23 publications
1
11
0
8
Order By: Relevance
“…This is in line with data from a previous study indicating that ‘feeling shy to take iron chelators in front of others’only slightly contributed to poor adherence in adolescents. 12 A vast array of technologies have been suggested as tools to improve drug adherence in young patients, but these technologies may not work well in countries where mobile phones are not allowed in classrooms, as in some schools in Thailand. 19 , 20 Drug use calendars represent a more appropriate low cost, simple and portable solution to improving drug use adherence in this situation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in line with data from a previous study indicating that ‘feeling shy to take iron chelators in front of others’only slightly contributed to poor adherence in adolescents. 12 A vast array of technologies have been suggested as tools to improve drug adherence in young patients, but these technologies may not work well in countries where mobile phones are not allowed in classrooms, as in some schools in Thailand. 19 , 20 Drug use calendars represent a more appropriate low cost, simple and portable solution to improving drug use adherence in this situation.…”
Section: Discussionmentioning
confidence: 99%
“… 7 Previous studies have revealed adherence rates to deferoxamine, deferiprone and deferasirox in paediatric patients of 59-83.3%, 79-98%, and 90-95%, respectively. 8 - 12 These studies employed several different methods to assess adherence including patient interviews to ask about adherence, pill or vial counts, self-assessment by patients, and serum ferritin level. It has been suggested that education and counseling interventions that include pill box count, diaries, and pharmacist-provided services improve iron chelation therapy adherence, 9 , 13 and in one study, using multiple interventions in combination appeared to result in a higher adherence rate.…”
Section: Introductionmentioning
confidence: 99%
“…Non-oral ICT can substantially affect HRQoL due to frequent, often daily, administration through a subcutaneous pump for at least 8-10 consecutive hours. This generally occurs during the night, with the potential to impair sleep, and is also associated with pain at the site of injection [46,47]. Oral ICT is preferred by patients, which leads to better adherence [48][49][50] and (possibly) QoL [14].…”
Section: Article Highlightsmentioning
confidence: 99%
“…The dose of ICT must be adjusted for each patient and careful regular monitoring is required to manage the adverse effects, such as nausea, joint pain, kidney injury, and agranulocytosis, which may be associated with treatment and may compromise adherence [8,9,17,52,53]. Additionally, over time, comorbidity due to iron overload and transfusion complications is likely to lead to polypharmacy, which has been shown to be a major issue for patients who do not adhere to ICT [47]. Other concerns with ICT use reported by both adhering and non-adhering patients include the high cost and the lack of immediate results from ICT [47].…”
Section: Article Highlightsmentioning
confidence: 99%
See 1 more Smart Citation